Abstract concepts: Libras/Portuguese translation and interpretation - Machado (UCS), Flávia Medeiros Álvaro (ANTARES: Letras e Humanidades, 2015)
The aim of the study is to identify the cognitive-linguistic processes in the translation activities from Portuguese to Libras by translators-interpreters; and from this to the comprehension expressed initially in Libras and, thereafter, in written Portuguese by deaf individuals. This translation process uses micro-texts, which specially designed for this purpose and sufficiently contextualized to ensure pragmatic consistency. This research intended to raise hypotheses and empirical evidences that lead to the improvement of the Libras translator-interpreters' competence, in the comprehension processes and in elaborating constructions that express abstract concepts which have lexical/grammatical correspondents in Portuguese, but not necessarily in Libras. Research findings reinforce the need for continued improvements of such professionals, and advises them on the problems of interpretation and translation of abstract concepts/as well.